HUBUNGAN PENGETAHUAN PENGOLAHAN MAKANAN DENGAN KETERAMPILAN MENGOLAH MAKANAN INDONESIA PADA SISWA SEKOLAH MENENGAH KEJURUAN - Nurul Ridhi Utami (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2017)
The objectives of this study are to determine the knowledge of learners of food processing, skills of learners to process Indonesian food, the relationship of food processing knowledge with the skills of processing food Indonesia. This study includes ex post facto research. Instrument result data tested validity and reliability, data analysis technique using Product Moment correlation. The results showed that the knowledge of food processing in sufficient category, the skills of processing Indonesian food in the category enough, there is a positive relationship and significant knowledge of food processing with food processing skills of Indonesia. The determinant coefficient (RÂ²) is 0.283, meaning that the contribution given by food processing knowledge to Indonesian food processing skill is 28.3%, while the remaining 71.7% is influenced by other factors.Keywords: food processing knowledge, Indonesian food processing skills